1998
DOI: 10.1051/aas:1998155
|View full text |Cite
|
Sign up to set email alerts
|

AU Monocerotis–improved elements

Abstract: Abstract. From an analysis, using Wilson-Devinney method, of the corrected yellow light curve of the semi detached eclipsing binary system AU Monocerotis (AU Mon), obtained by Lorenzi (1980b), an improved value for the mass ratio, q, equal to 0.1985 and reliable geometrical elements were derived.They give the absolute elements as: m h /m = 5.93 ± 0.31; m c /m = 1.18 ± 0.16; R h /R = 5.28 ± 0.16; R c /R = 10.04 ± 0.74; Log L h /L = 3.16 ± 0.14; Log L c /L = 2.07 ± 0.21; Log g h = 3.76 ± 0.06; and Log g c = 2.51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The rate of mass transfer may change periodically due to the oscillations of the donor star around its critical Roche lobe, causing changes in the size and density of the accretion disc and/or circumbinary matter. Vivekananda & Sarma (1998), who studied the photoelectric measurements of Lorenzi (1980b), using a similar semidetached model as Desmet et al (2010), suggested that the long‐term variation may be due to the precession of the accretion disc around the gainer, caused by the gravitational perturbations by the donor.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of mass transfer may change periodically due to the oscillations of the donor star around its critical Roche lobe, causing changes in the size and density of the accretion disc and/or circumbinary matter. Vivekananda & Sarma (1998), who studied the photoelectric measurements of Lorenzi (1980b), using a similar semidetached model as Desmet et al (2010), suggested that the long‐term variation may be due to the precession of the accretion disc around the gainer, caused by the gravitational perturbations by the donor.…”
Section: Resultsmentioning
confidence: 99%
“…The physical parameters of these active regions have similar values to those found in other active binaries. Vivekananda Rao et al (1991) pointed out a progressive decrease in the brightness of the system since the observations of Chambliss (1965). WY Cnc was included in the UV survey carried out by Budding et al (1982) and displayed higher emission in Mg II h and k lines than is found in the Sun.…”
Section: Higher Resolution Ha Observationsmentioning
confidence: 90%
“…A few years later, WY Cnc was considered as RS CVn short-period system (Hall 1976) because of the irrergularities observed in its light curves, as well as the emission displayed by the primary component in the Ca II H and K lines (Popper 1976). Since then, WY Cnc has not been regularly observed, although some authors have published visible light curves (for references, see Zeilik et al 1990 ;Vivekananda Rao, Sarma, & Prakash Rao 1991 ;Heckert et al 1998). The Ðrst infrared light curves were observed by & (1990) and Zeilik et al Are valo La zaro (1990).…”
Section: Higher Resolution Ha Observationsmentioning
confidence: 99%
“…The value of the orbital period of ZZ Boo (nearly 5 days) allows us to estimate the synchronization time to be close to 10 6 years; hence, the components have to be synchronized at the pre-main-sequence stage like the case of SZ Psc. Synthetic spectra were calculated with parameters T effA = 15,000 K, log g A = 3.5 and T effB = 6000 K, log g B = 2.5 (Vivekananda & Sarma 1998).…”
Section: S Cnc Rx Gem Au Mon Ry Gem Rz Eri Zz Boo and Sz Psc-symentioning
confidence: 99%